Temperature-sensitive, protoplast-forming os-1 varient of Neurospora- a few tricks. - C. P. Selitrennikoff (Fungal Genetics Reports, 1982)
Temperature-sensitive, protoplast-forming os-1 varient of Neurospora- a few tricks.